2010
DOI: 10.1186/1756-0500-3-53
|View full text |Cite
|
Sign up to set email alerts
|

Detection of siRNA induced mRNA silencing by RT-qPCR: considerations for experimental design

Abstract: BackgroundRNA interference (RNAi) has been one of the most rapidly expanding areas of biological research in the past decade, revolutionizing the ability to analyze gene function. Thorough validation of siRNA duplexes is required prior to use in experimental systems, ideally by western blotting to show a reduction in protein levels. However, in many cases good antibodies are not available, and researchers must rely on RT-qPCR to detect knockdown of the mRNA species.FindingsWe have observed a phenomenon that gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 12 publications
(12 reference statements)
4
37
0
Order By: Relevance
“…S5). Similar variable qPCR results were previously reported for silenced genes and could be caused by incomplete degradation of mRNA fragments (Shepard et al, 2005;Holmes et al, 2010). Expression analysis in subsequent generations was further complicated by the limited survival and fertility of these seedlings, and by the reversion of the surviving lines to the characteristic DEX-dependent overexpression phenotypes in the subsequent generation.…”
Section: Cosuppression Of Hdg Expression Results In Overproliferationsupporting
confidence: 63%
“…S5). Similar variable qPCR results were previously reported for silenced genes and could be caused by incomplete degradation of mRNA fragments (Shepard et al, 2005;Holmes et al, 2010). Expression analysis in subsequent generations was further complicated by the limited survival and fertility of these seedlings, and by the reversion of the surviving lines to the characteristic DEX-dependent overexpression phenotypes in the subsequent generation.…”
Section: Cosuppression Of Hdg Expression Results In Overproliferationsupporting
confidence: 63%
“…In accordance with our expectations, we found that the injection of hsp83 dsRNA into A. pisum reduced the lifespan, fecundity, and number of viviparous offspring, even though the attenuation of HSP83 expression was not significant. The confirmation of gene knockdown in RNAi experiments is sometimes difficult, particularly if the target gene is expressed at a low level, because it depends on the selected reference genes (Holmes et al 2010; Baumann et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…siRNA cleavage fragments persist after cleavage, although it was observed that this does not occur for all mRNAs for reasons not yet clear (18,20).…”
Section: Discussionmentioning
confidence: 86%
“…In mammalian cells mRNA degradation has been observed to be neither rapid nor complete with siRNA-mediated cleavage reported to result in the generation of partially stable 5' or 3' mRNA fragments (17)(18)(19)(20). Indeed, we have previously shown that truncated proteins can be translated from the 5' end of shRNA-targeted mRNA (21).…”
Section: Introductionmentioning
confidence: 95%